Synthesis, Characterization and DFT Study of 4,4′-Oxydianiline Imines as Precursors of Tetrahalo-1,3-oxazepine-1,5-dione - Abdullah Hussein Kshash; Mohammed Ghannam Mokhlef (Universitas Gadjah Mada, 2017)
This work presents four Schiff bases derived from 4,4′-Oxydianiline, distinguished by the para substituted halogen of benzaldehyde. These bases were used to synthesize eight compounds of di-1,3-oxazepine by direct condensation with tetrachloro phthalic anhydride and tetrabromo phthalic anhydride. The reactions were monitored with TLC and all structures were characterized using spectroscopic techniques such as FT-IR, 1H-NMR, 13C-NMR and C, H, N techniques. On the other hand, a theoretical study by Density Functional Theory (DFT) for the electronic structures was intended to study the effects of para-substituted halogen of benzaldehyde on the electronic structure of synthesized Schiff bases by using the Gaussian program. Theoretical results indicate that there is no effect of halogen atoms except for bromine on HOMO and LUMO energies of the synthesized compounds.